Production of genome-edited Daphnia for heavy metal detection by fluorescence - Takuto Arao (Nature Portfolio, 2020)
Abstract Aquatic heavy metal pollution is a growing concern. To facilitate heavy metal monitoring in water, we developed transgenic Daphnia that are highly sensitive to heavy metals and respond to them rapidly. Metallothionein A, which was a metal response gene, and its promoter region was obtained from Daphnia magna. A chimeric gene fusing the promoter region with a green fluorescent protein (GFP) gene was integrated into D. magna using the TALEN technique and transgenic Daphnia named D. magna MetalloG were produced. When D. magna MetalloG was exposed to heavy metal solutions for 1 h, GFP expression was induced only in their midgut and hepatopancreas. The lowest concentrations of heavy metals that activated GFP expression were 1.2 µM Zn2+, 130 nM Cu2+, and 70 nM Cd2+. Heavy metal exposure for 24 h could lower the thresholds even further. D. magna MetalloG facilitates aqueous heavy metal detection and might enhance water quality monitoring.